Enacting Life-Based Learning (LBL) Approach in Quantitative Research Methodology Course: The Case of Biology Education Students - Herawati Susilo; Sri Rahayu Lestari; Betty Lukiati (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2019)
This study portrayed the enactment of Life-Based Learning (LBL) in quantitative research methodology course among Master’s students in biology education. Literature study and action research were employed to capture data. The literature study attempted to unveil how LBL was performed. Furthermore, the action research was in the form of Lesson Study (LS) to carry out the course outline. Practically, characteristics of LBL were performed using authentic materials. These were in the forms of filling out questionnaire of first semester intake, doing peer L, developing mind/concept mapping, assessing peers’ mind/concept mapping, assessing peer portfolio, writing learning journal, doing critical analysis on journal articles, developing research proposal, assessing peers’ critical analysis and performance, uploading files of mind/concept mapping, and presenting critical analysis works. From the action research lens, different-class students preferred varied strategies for similar learning materials and they favored such processes.